SOCIAL AND PHILOSOPHICAL ASPECT OF MODERN TECHNICAL UNIVESITY - Ченбай, Н. А. (Proceedings of the National Aviation University Series Philosophy Cultural, 2015)
The articles an analysis of the modern technical university.